ABDULLAH BIN ELIAS AL-KILIKORY (T1099) HIS APPROACH OF HIS BOOK: EXPLANATION OF AL-IZI TEXT IN MORPHOLOGY - Uday Anad Shukri; Laith Qahir Abdullah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The language has received special attention from the scholars of nations to preserve it, to upgrade it, and to rid it of the impurities that hang with it over time, because it is a manifestation of civilization for any nation, the civilizations of nations are measured in their languages, and the extent to which they understand what human thought produces in various fields of science. The Book (Explanation of the Discharge of The Azi): Abdullah al-Kalkuri is one of the important exchange books that had to be taken out to the public to benefit from it. The book is illustrated by the unique mentality of this venerable world, which was a beacon for the people of its time in science. Sheikh May God rest his soul on many of the opinions of his predecessors, such as Hebron, Sibweh, Al-Akhfash, Zamakhshari, Ibn Juni, and many others. The book was easy, clear in its words, phrases, and examples, and the ease of the method was connected to the desired presentation in a way that attracted the reader.